Body mass index, lipid profile, and hypertension contribute to prolonged QRS complex. (August 2022) - Sobhani, Sahar; Raji, Sara,; Aghaee, Atena; Pirzadeh, Parisa; Ebrahimi Miandehi, Elahe; Shafiei, Susan; Akbari, Masoumeh; Eslami, Saeid
Summary: Background and aims: : QRS prolongation is one of the most common findings in patients with underlying cardiac diseases. Recent studies have shown that QRS prolongation can be accompanied by obesity, hypertension, and hyperlipidemia, which are known risk factors for cardiovascular events. This study aimed to evaluate how obesity, hypertension, and hyperlipidemia could affect QRS duration. Methods: A total of 4033 eligible subjects aged between 35 and 70 years were included from the Persian Cohort Study in Mashhad. ECG intervals, blood pressures, lipid profile, and BMI measures were obtained at the time of enrolment. Multiple regression analysis was performed to assess the relationship between QRS duration and BMI, hypertension, and lipid profile. Results: This study population consisted of 2047 females and 1986 males with a mean age of 46.05 ± 9.50 years. Higher BMI values and heart rate were observed in women (27.12 ± 4 and 74.66 ± 8.54; P  < 0.001), while height, weight, and QRS duration showed a significant increase in men (172.60 ± 7.18, 79.44 ± 12.55, and 97 ± 11.05; P  < 0.001). Except for total cholesterol ( P  = 0.317), blood pressures and lipid profile differed significantly among women and men ( P  < 0.001). Furthermore, univariate analyses indicated that QRS duration was associated with age, sex, triglycerides, high-density lipoprotein (HDL), low-density lipoprotein (LDL), systolic blood pressure, diastolic blood pressure, categorical blood pressure, categorical BMI, and continuous BMI. On the backward multivariate model, TG, LDL, HDL, DBP, SBP, categorical blood pressure, categorical BMI, and continuous BMI were independently correlated with QRS duration. Conclusions: Hypertension, increased BMI, and high levels of LDL, TG, and lower HDL, as well-known risk factors of cardiovascular disease, were associated with prolonged QRS duration. These findings could be beneficial in future investigations regarding establishing the underlying heart problems.